2022
DOI: 10.3390/ijerph19095655
|View full text |Cite
|
Sign up to set email alerts
|

Pet Ownership and Mental and Physical Health in Older White and Black Males and Females

Abstract: Pet ownership literature remains mixed regarding associations with mental and physical health outcomes among older adults. The present study investigates the relationship between pet ownership and depression, health, and physical activity in an older adult sample balanced by sex (male/female), race (White/Black), and urban/rural status. Participants were adults aged 65+ recruited between 1999 and 2001 in the University of Alabama at Birmingham Study of Aging. Participants completed the Geriatric Depression Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Interestingly, an early study, in 2006, by Thorpe et al [39] found that dog owners differed in terms of physical activity compared to those non-pet owners, however those pet owners that were not dog walkers did not differ from non-pet owners. Furthermore, a study by Albright, Cui, and Allen [9] found that dog owners had better subjective health and were more likely to take part in exercises such as walking than their non-pet owner counterparts. Shibata et al [31] reported how important physical activity was in older adults and that those pet owners who had dogs were more likely to be sufficiently active than non-pet owners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, an early study, in 2006, by Thorpe et al [39] found that dog owners differed in terms of physical activity compared to those non-pet owners, however those pet owners that were not dog walkers did not differ from non-pet owners. Furthermore, a study by Albright, Cui, and Allen [9] found that dog owners had better subjective health and were more likely to take part in exercises such as walking than their non-pet owner counterparts. Shibata et al [31] reported how important physical activity was in older adults and that those pet owners who had dogs were more likely to be sufficiently active than non-pet owners.…”
Section: Discussionmentioning
confidence: 99%
“…In older adults, pet ownership may increase when they reach retirement age, as the individuals now have more time to give to a pet. Ageing research on older adults and pet ownership suggests that there are positive benefits on mental and physical wellbeing with pets helping emotional and social needs [8][9][10][11][12]. Friedmann et al [11] reported that pet ownership was associated with better cognitive function and physical function than those who did not own pets or had no regular contact with pets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these potential benefits of pet ownership, few studies have investigated the benefits of owning pets among community-dwelling older adults ( Hughes et al, 2020 ; Albright et al, 2022 ). Most research investigating such relationships has focused on the therapeutic effects of animal-assisted therapy in patients with memory disorders ( Kanamori et al, 2001 ; Bono et al, 2015 ) or those who need care in nursing homes ( Stasi et al, 2004 ; Colombo et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Companion animals can transmit potential pathogens to humans, and especially elderly people (> 65 years) are more susceptible to the risk of pet-induced zoonosis. [2,3] On the upside, this age group bene ts most from taking care of a pet due to the positive in uence it has on mental and physical health [4], such as decreased feelings of loneliness and anxiety [5]. Research showed that older pet owners are less concerned about the risk of zoonotic transmission of disease [6], yet they are more susceptible to health problems occurring after infection.…”
mentioning
confidence: 99%